Kinematic analysis of javelin throwing - Lo, T. Y.; Chou, Y. C.; Chen, Y.; Chang, J. H. (14th International Symposium on 3D Analysis of Human Movement, 2016)
Purposes: To investigate the difference between the best grade trial (B)and the worst grade trail (W) of the javelin throwing. Methods: Six elite male javelin throwers served as the subjects of this study. Each one had to throw javelin 6 times. Vicon Motion System was used to collect data, and Visual 3D was used to measure the kinematic parameters. The best and worst grades trails were chosen for statistics analysis. Wilcoxon matched-pairs signed-ranks test was used to test the trunk angle, right shoulder joint angle, right elbow joint angle, right and left knee joint angle, javelin release angle, javelin release speed and javelin release height. The á value was set as .05. Results: There is no difference between two trials in trunk angle and other joint angles. Conclusion: The joint angle mentioned in this study were not the key that result in grades variate at elite throwers.